The social pay gap across occupations: Survey and experimental evidence - Elisabeth Bublitz; Tobias Regner (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2016)
Receiving equal wages for work of equal value is a legal right in many countries. However, it remains unknown to what degree the neglect of this principle yields differences in pay between social and other occupations. The results of a task-based analysis with survey data confirm a notable wage penalty of 0.5 standard deviations for social occupations (e.g., health care, education). Based on these results, we design a laboratory experiment that mimics actual income distributions (Germany, USA), incorporates social occupations in the lab society, and allows for (voluntary) redistribution among subjects. The results show that, regardless of (non-)random assignment to social jobs and the level of income inequality, individuals in social jobs are only partly compensated for their social effort. A downward spiral, induced by emotional reactions, results as social effort and donations converge to a 'low' equilibrium. This suggests that a market approach fails to eliminate the social pay gap.
Keywords: C90; D62; D63; H23; J31; 330; inequality; tasks data; redistribution; experiment; voluntary payments; social returns; externality